Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena Memorandum of Understanding Signing Ceremony Between UMP and Malaysia Institute of Corporate Governance - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
While the forum that we just had was the prelude to the inauguration of the FIM’s Governance & Integrity Centre (FGIC) by the Menteri Besar of Pahang later this afternoon, the conclusion of the Memorandum of Understanding (MoU) between UMP and the Malaysian Institute of Corporate Governance (MICG) is another strategic move to enhance the role, function and capacity of FGIC at this early stage.